Screen Out Anaemia Among Adolescent Boys as Well! - Dheeraj Gupta; Bhawana Pant; Ranjeeta Kumari; Monika Gupta (National Journal of Community Medicine, 2013)
Background: Adolescence – a period of transition between childhood and adulthood is a significant period of human growth and maturation. Adolescents represent about a fifth of India’s population. Many studies in recent times have highlighted the high prevalence of anaemia among adolescent girls in India; however, there is limited published literature on prevalence of anaemia among adolescent boys.